2016
DOI: 10.1051/0004-6361/201526095
|View full text |Cite
|
Sign up to set email alerts
|

Models of quasi-periodic oscillations related to mass and spin of the GRO J1655-40 black hole

Abstract: Frequencies of the three quasi-periodic oscillation (QPO) modes observed simultaneously in the accreting black hole GRO J1655-40 are compared with the predictions of models. Models in which all three QPO signals are produced at the same radius are considered: these include different versions of relativistic precession, epicyclic resonance, tidal disruption, and warped disc models. Models that were originally proposed to interpret only the twin high-frequency QPOs are generalized here to interpret also the low-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 44 publications
(83 reference statements)
2
50
0
Order By: Relevance
“…The models of twin HF QPOs involving the orbital motion of matter around black hole can be generally separated into four classes: the hot spot models (the relativistic precession model and its variations [39,49], the tidal precession model [25]), resonance models [48,50,51] and disk oscillation (diskoseismic) models [29,35]. These models were applied to match the twin HF QPOs and the LF QPO for the microquasar GRO J1655-40 in [47]. Of course, the models can be applied also for intermediate massive black holes [44].…”
Section: A General Properties Of Qpos and Constraints Of Black Hole mentioning
confidence: 99%
“…The models of twin HF QPOs involving the orbital motion of matter around black hole can be generally separated into four classes: the hot spot models (the relativistic precession model and its variations [39,49], the tidal precession model [25]), resonance models [48,50,51] and disk oscillation (diskoseismic) models [29,35]. These models were applied to match the twin HF QPOs and the LF QPO for the microquasar GRO J1655-40 in [47]. Of course, the models can be applied also for intermediate massive black holes [44].…”
Section: A General Properties Of Qpos and Constraints Of Black Hole mentioning
confidence: 99%
“…are considered. The ERM, originally developed to interpret only the twin HF QPOs, has been extended to interpret the LF QPO mode in terms of ν nod (as in the RPM), and thus interpret the simultaneous occurrence of the three frequencies associated with GRO J1655-40 (Stuchlík & Kološ 2016). Among all possibilities discussed by these authors, we consider here the case in which the two HF QPOs are identified with ν upper = ν θ and ν lower = ν − .…”
Section: Geodesic Models Of Qposmentioning
confidence: 99%
“…The frequencies of quasiperiodic oscillations in the Schwarzschild metric were studied for example in [16,17], while for the Kerr metric they have been studied in various physical scenarios, for example in [18][19][20]. The application to astrophysics and the study of astrophysical black holes was discussed in [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%